Three-dimensional inhomogeneities in PEDOT:PSS films - Kemerink, Martijn; Timpanaro, Salvatore; de Kok, M. M.; Meulenkamp, E. A.; Touwslager, F. J. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2004)
Spin-cast PEDOT/PSS film are investigated using scanning probe-based spectroscopic techniques. The films are found to consist of relatively well-conducting islands that are embedded in a less conductive matrix. A scanning-tunneling microscope-based method is developed to obtain three-dimensional conductivity images with nanometer resolution. Order-of-magnitude variations in the film conductivity are observed in all spatial directions. In addition, charge transport in the normal direction depends on the injection spot and is found to be ohmic or space-charge-limited. We found that both the morphology and the conductivity of the top layer differ substantially from those in the bulk, which is attributed to an enhanced PSS content in the top layer.
Gesehen am 16.12.2019